EKSPLORASI AKUIFER AIR BAWAH TANAH MENGGUNAKAN METODE TAHANAN JENIS 2D DI DESA SELARU KABUPATEN KOTABARU, KALIMANTAN SELATAN - Rudy Hendrawan Noor; Ishaq Ishaq; Jarwanto Jarwanto; Dwi Priono (AL-ULUM: JURNAL SAINS DAN TEKNOLOGI, 2020)
Geoelectric resistivity method is one method that can be used to characterize water-bearing rock layers (aquifers). This method is based on the existence of differences in type resistivity in the layers of rock that are flowed electrically. The use of this method is based on easy application, faster data acquisition with broad data coverage (lateral and vertical), and lower costs. Data acquisition uses two configurations or electrode arrangement, namely sclumberger and wenner-schlumberger configurations. The number of trajectories for data acquisition uses one path with a total of 28 electrodes and the spacing between the electrodes is 20 meters. The data obtained in the form of data resistivity type of each underground layer and its depth will be further analyzed using AGISSAdmin software. The results are obtained in the form of a 2-dimensional (2D) cross-sectional value of underground layers laterally and vertically. The low resistivity value will be interpreted as a layer containing ground water, which was previously corrected against the geological and hydrological data of the area. From the cross section of the type resistors, values of 20 - 317 Ωm were obtained for the wenner and wenner-schlumberger arrangements. Selaru Village consists of two rocks unit, the first rock (≤ 120 Ohm.m) in the form of Tanjung Formation rocks, with large porosity and small permeability and groundwater potential in this unit is small (0 - 40 m depth). The second rock (≥ 120 Ohm.m) is Pre Tertiary, with very little porosity and permeability, except secondary porosity in rock fractures.